Pendampingan Manajemen Kewirausahaan di Pondok Pesantren Dalam Pemberdayaan Ekonomi Masyarakat - Fahrina Yustiasari Liriwati; Mulyadi, Abdul Syahid (Adiba Aisha Amira, 2021)
The purpose of this community service is to increase the knowledge and skills of the Sabilal Muttaqin Islamic boarding school students, Indragiri Hilir Regency, Riau Province. Increasing awareness in the use of cottage land and its management of cleanliness; increasing the insight of students so that they can generate motivation and enthusiasm for entrepreneurship; increasing the economic value of natural resources in Islamic boarding schools. The methods used are lectures, training and mentoring, covering material on entrepreneurship, land management and chili cultivation. The results of this activity have increased the entrepreneurial insight of students, as well as skills in utilizing the potential of local raw materials for products with more economic value and understanding of the application of more effective technology to strengthen the characteristics of entrepreneurial boarding schools